Prevalence and biochemical correlates of microalbuminuria in type 2 diabetes mellitus at Puducherry, India - Hussain, K. Shaik Anwar (International Journal of Advances in Medicine, 2018)
Background: Microalbuminuria is a risk factor for end stage renal disease as a sequalae of diabetic nephropathy and an independent risk factor for cardio-vascular diseases. Early screening for Microalbuminuria can prevent long-term complications. The objective of the present investigation was to study the magnitude of Microalbuminuria among the patients with type 2 diabetes mellitus attending to the diabetic clinic and correlate with other biochemical parameters related to complications of diabetes. Methods: This observational study was conducted among 500 type 2 diabetic patients attending to the diabetology OPD, Department of General medicine during the time period June 2017 to May 2018. The patients were interviewed for socio-demographic details, history and clinical examination and subjected to blood investigations and ECG. Results: Microalbuminuria was present in 31.6% (n=158) of the diabetics. Age group 45-55 years, male gender, duration of diabetes >10 years, active smokers, Diabetic retinopathy, Peripheral neuropathy, Ischemic heart disease, SBP 160-170 mmHg, DBP 95-100 mmHg and 100-105 mmHg, BMI 30-35 Kg/m2, TG >250 mg/dl, LDL >110 mg/ dl and HbA1c 7.5-9 % showed a greater odds ratio and significant association (p<0.001) with Microalbuminuria. Conclusions: There was an increased prevalence of Microalbuminuria among the patients with type 2 diabetes. It also showed significant association of major microvascular and macrovascular complications of diabetes and Microalbuminuria.